2021
DOI: 10.3390/jcm10030458
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Endothelial Cell Dysfunction and Neuroretinal Degeneration in Diabetic Patients

Abstract: Diabetes mellitus (DM) has become a vital societal problem as epidemiological studies demonstrate the increasing incidence of type 1 and type 2 diabetes. Lesions observed in the retina in the course of diabetes, referred to as diabetic retinopathy (DR), are caused by vascular abnormalities and are ischemic in nature. Vascular lesions in diabetes pertain to small vessels (microangiopathy) and involve precapillary arterioles, capillaries and small veins. Pericyte loss, thickening of the basement membrane, and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 118 publications
1
49
0
Order By: Relevance
“…Further progression of BM thickening in DR leads to ischemia and retinal capillaries degeneration. 49 All treatment groups showed a highly significant decrease in BM thickness compared to the DR control group (p<0.05) with the HA-coated NPs, either topical or IVT reaching a comparable thickness to the normal control group (0.09 µm).…”
Section: Resultsmentioning
confidence: 83%
“…Further progression of BM thickening in DR leads to ischemia and retinal capillaries degeneration. 49 All treatment groups showed a highly significant decrease in BM thickness compared to the DR control group (p<0.05) with the HA-coated NPs, either topical or IVT reaching a comparable thickness to the normal control group (0.09 µm).…”
Section: Resultsmentioning
confidence: 83%
“…Childhood diabetes is a risk factor for a serious chronic disorder (e.g., nephropathy, retinopathy, peripheral neuropathy, and dermopathy) [ 19 , 20 ]. Macular and RNFL thicknesses analysis may identify early changes prior to the development of diabetic-related microvasculopathy [ 12 , 21 , 22 ]. Our study demonstrated the differences in macular and RNFL thicknesses between South East Asian children with T1DM and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Human ischemic retinal diseases and their animal models, including diabetic retinopathy (DR), retinopathy of prematurity (ROP), and retinal vein occlusions (RVO), all involve increased neural cell death, sterile inflammation, and vascular permeability [ 1 5 ]. Vision loss in these ischemic diseases is associated with vascular permeability leading to macular edema [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%